Development and Testing of a Weakly Rigid Gear Transmission Test Platform - Liang Jie; Sun Guangyao (Jixie chuandong)
In order to conduct a more in-depth and detailed study of gearing systems, based on vibration characteristics of weakly rigid gear transmission shafts, a high-precision laser displacement sensor is proposed for the vibration measurement of transmission shafts, a gear test bench is developed for testing weakly rigid gear transmission systems, and vibration testing research is carried out for weakly rigid gear transmissions under different working conditions. Based on the low critical speed of the weakly rigid gear drive, a modal analysis of the rotor consisting of gears and shaft is carried out to obtain the inherent frequency of the rotor and calculate the motor speed at which the rotor resonance may be triggered. This is verified by a constant load variable speed test and a constant speed variable load test. The results show that the system reaches the resonant frequency of the rotor at a motor speed of around 219.69 r/min. Analysis of the data reveals that the shaft vibration amplitude is linear in response to the load over a range of values and is not significantly affected by the speed. Finally, repeatability tests are carried out on the test rig to verify the reliability and stability of the equipment.